Utilization of Android-based Myting Program in Improving Myob Accounting Learning Outcomes for Students At SMK Muhammadiyah 04 Medan - Lola Fadhillah; Dongoran, Faisal Rahman; Khairani, Suci (Aksaqila International Humanities and Social Sciences [AIHSS] Journal, 2024)
The purpose of this study was to determine the use of Myting Program can improve the learning outcomes of students of SMK Muhammadiyah 04 Medan and to determine the improvement of learning outcomes after using Myting Program in students of SMK Muhammadiyah 04 Medan. The approach in this study using quantitative research and this research uses the type of experimental research, research design with Quasi Experimental Design type Nonequivalent Control Group Design. Samples taken 2 classes which The samples taken were 2 classes which were divided into two groups, namely class XI AKL 1 as a control group with a total of 38 students and an experimental group of class XI AKL 2 with a total of 36 students. The results showed that the results of the Wilcoxon test conducted in the experimental class and control class were 0.000. This means that there is a difference between the pre-test and post-test scores in the experimental and control classes, which is smaller than Sig.???? = 0.05 (0.00 < 0.05). Hypothesis testing in this study used the Mann-Whitney test with the value obtained that Zhitung was -5,254 with a Sig value of 0.000. The significance value is smaller than 0.05 so that based on the decision-making criteria Ha is accepted. This shows that the average increase in MYOB Accounting learning outcomes of experimental class students is greater than the control class. So the result is that there is an increase in student learning outcomes after using the Android-based Myting program. Android-based Myting program for students at SMK Muhammadiyah 04 Medan.